Assessing Awareness, Attitudes, and Practices of Undergraduate Management Students Toward Green and Sustainable Public Health Initiatives - Khatiwada, Bipana; Rana, Roshani (International Journal of Atharva, 2026)
Background: The inclusion of environmental sustainability in public health, known as Green and Sustainable Public Health Initiatives (GSPHI), is very important for dealing with modern-day challenges in the global scenario. As future leaders in organizations, the readiness of undergraduate management students to support GSPHI is very important, but their AAPs are not well studied, especially in a Nepal scenario.Objectives: This study was designed to evaluate the AAPs of undergraduate management students towards GSPHI, explore the relationships between awareness, attitudes, and practices, investigate their effects on future intentions, and determine the contributing demographic factors.Methods: A quantitative, cross-sectional study was carried out among 202 undergraduate management students from a Pokhara University-affiliated college in Kathmandu, selected through convenience sampling. The data were collected through a structured, 25-item questionnaire covering five domains: Awareness, Personal Engagement, Perception of Corporate Social Responsibility (CSR), Attitudes Towards Policy and Governance, and Future Intentions and Advocacy.Findings: Students demonstrated moderately high awareness (mean scores: 3.50–4.13) and strongly positive attitudes towards policy (means: 4.00–4.18) and CSR (means: 3.96–4.15). Personal engagement was moderate (means: 3.57–3.73). Future intentions were high (means: 3.86–4.15). Regression analysis revealed that Attitudes Towards Policy and Governance (β=0.436, p